Plastmasas otrreizēja pārstrāde konkurētspējīga produkta izveidei jaunā uzņēmumā - Aizpurietis, Andis (Latvijas Universitāte, 2018)
Maģistra darba „Plastmasas otrreizēja pārstrāde konkurētspējīga produkta izveidei jaunā uzņēmumā” mērķis ir veicināt izlietotās plastmasas pārstrādi Latvijā. Maģistra darbs ietver plastmasas ražošanas nozares attīstības analīzi un risinājumu piedāvājumu, kurā par pamatu tiek ņemts atsevišķs plastmasas produkta virziens – plastmasas galda spēļu ražošana. Uzņēmuma mērķis ir nodrošināt Latvijas iedzīvotājus līdz 2020. gadam ar vismaz vienu konkurētspējīgu alternatīvu no pārstrādātas plastmasas.

The aim of Master thesis " Plastic recycling for making a competitive product in new company” is to increase the indicators of recycling level of used plastic products. Master thesis includes the analysis of plastic production industry development and provides the solution which is based on plastic board game production. The present research defines the following problem: the amount of used plastic in landfills and environment is very high. Examining this problem, the author has developed the current project. During the present research, a new company was established, as well as necessary production equipment was purchased and installed. The company's goal is to supply Latvian residents with at least one competitive alternative product made from recycled plastic till year 2020.
Plastic recycling for making a competitive product in new company
Keywords: Vadībzinātne; projektu vadīšana; projekts; plastmasas pārstrāde; plastmasas ražošana